Wenyang Zhenshuai Granules inhibits cardiomyocyte apoptosis in chronic heart failure by regulating p38 MAPK signaling pathway through exosomal miR-155 - Peng, Liqi; Chen, Xinyu; Cai, Huzhi; Tang, Yanping; Chen, Qingyang; Zhou, Fang (Frontiers in Pharmacology, 2025)
BackgroundChronic heart failure (CHF) represents a significant global public health concern, warranting further investigation and intervention. Wenyang Zhenshuai Granules (WZG) is an in-hospital preparation of the First Affiliated Hospital of Hunan University of Chinese Medicine, which has been approved by the Hunan Provincial Drug Administration (Approval No.: Z20190105000) for the treatment of CHF. The objective of this study was to examine the impact of WZG on cardiomyocyte apoptosis in CHF through the regulation of the p38 mitogen-activated protein kinase (MAPK) signaling pathway by exosomal microRNA-155.MethodsDoxorubicin (DOX) was employed to construct a model of cardiomyocyte injury associated with CHF. The H9c2 cells were divided into four groups: the normal control group (NC), the DOX group (DOX), the DOX + drug-containing serum group (DOX+WZG), and the DOX + enalapril (ENP) group (DOX+ENP). The morphology of the cardiomyocytes was observed at 15, 30, and 45 h into the experiment using an inverted microscope. The viability of cells and the number of apoptotic cells were determined through the use of a CCK-8 assay and flow cytometry, respectively. Subsequently, exosomes were extracted and subjected to morphological characterization and identification. The expression of exosomal miR-155, the p38 MAPK signaling pathway, and apoptotic proteins were examined.ResultsThe results demonstrated that WZG could enhance the morphology of H9c2 cells, diminish the apoptosis rate of cells, and augment the viability of cells. Western blot and RT-qPCR assays provided further confirmation that WZG could promote the secretion of exosomes from cardiomyocytes, increase the content of miR-155 in exosomes, and inhibit the activation of the p38 MAPK signaling pathway.ConclusionWZG inhibits p38 MAPK protein phosphorylation via exosomal miR-155, thereby exerting anti-apoptotic effects on cardiomyocytes in CHF.